Internship at Colegio La Salle Montería (2023)
This report describes the internship process and results conducted at Colegio la Salle Montería. It consisted of teaching to nine graders. The main purpose of this internship was to provide a space in which the students could feel comfy to express and interchange their opinions through directed conversations or a conversation club about interculturality and how does this work. This paper discusses the teaching practices, methodologies, results, conclusions and suggestions, and limitations of this meaningful experience.